Microcrack characterization in loaded CFRP laminates using quantitative two- and three-dimensional X-ray dark-field imaging. (December 2018) - Senck, Sascha; Scheerer, Michael; Revol, Vincent; Plank, Bernhard; Hannesschläger, Christian; Gusenbauer, Christian; Kastner, Johann
Abstract: In this work we present a method to characterize microcracks in carbon fiber reinforced polymer (CFRP) samples with a diameter up to 120 mm using quantitative grating-based X-ray dark-field imaging. In contrast to conventional microcomputed tomography (XCT), grating-based X-ray radiography and XCT provide three complementary images: (a) attenuation contrast (AC), (b) differential phase contrast, and (c) dark-field contrast (DFC). CFRP samples were subjected to low velocity impacts, followed by subsequent short beam bending tests. Using a multiscale approach, we assessed damage two- and three-dimensionally at voxel sizes of 12.5 µm, 22.8 µm, and 50 µm. Since DFC delivers morphological information in the sub-pixel regime it is possible to quantify defects in relatively large samples whereas microcracks are not visible in AC images. We compared our results to ultrasonic testing showing that X-ray dark-field imaging improves defect detection in CFRPs without the necessity of small sample dimensions.